THE EFFECT OF BALL HANDING AND WALL VOLLEYBALL TRAINING ON SUMBAWA CLUB DOWN PASSING SKILLS IN 2023 - Bima Votum Ade Yasa; Subakti; Nurdin (JOETAL: Journal of Education, Teaching and Learning, 2024)
Focus of this research problem is that in lower passes there are lots of inappropriate passes, so that lower passes are felt to be inaccurate, the way to do them is wrong and mistakes often occur in making these lower passes. Research bbjectives to find out if there is a difference the effect of ball handing and wall volleyball training on Sumbawa Club's lower passing skills in 2023. The research design used was experimental research "Two Groups Pretest-posttest Design". This type of research uses research. The implementation of this design is by providing treatment, in the form of ball handing and wall volleyball to the subject for a certain time, measuring bottom passing. In this research the researcher uses an instrument, namely the bottom passing test. In this study, the researcher used the entire population to be used as a research sample, namely the entire 2023 Sumbawa Volleyball Club, totaling 20 people. The sampling technique used a population study technique. Data analysis calculated t-value is greater than the t-table, (> 1.833), thus the "t" value obtained in this study is significant. Based on the test results and data analysis, it can be concluded that: (1) there is the influence of ball handing training on Sumbawa Club's lower passing skills in 2023, (2) there is the influence of wall volleyball training on the bottom passing skills of the Sumbawa Club in 2023 and (3) there is a difference the effect of ball handing and wall volleyball training on Sumbawa Club's lower passing skills in 2023.